Marketing Strategy of Sharia Pawn Products in Attracting Customer Interest - Mujibno; Sasi Rohmah Awalia (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2022)
The marketing strategy between sharia and conventional is very different in the process, but has the same goal, namely how to increase the number of customers. This study aims to determine the marketing strategy of sharia pawn products in attracting customers at the BMT Nu Pragaan Sumenep branch. This study uses qualitative methods, namely case studies and using techniques of observation, interviews, and documentation. The results of this study indicate that the marketing strategy for rahn products implemented by the BMT NU Pragaan Branch uses face-to-face communication via online, grebek pasar / field trips, supporting factors or facilities that assist managers in conducting marketing at BMT NU Pragaan Branch are Brochures and Website The official website contains complete information about all the products available at BMT NU. Marketing constraints for BMT NU Pragaan Sumenep branch in attracting customer interest, namely the number of competitors/competitors, but this does not affect customer interest because the number of customers continues to increase every year.